Temporal variability of chemical properties in a soil with three cultivation systems - Carvalho, Orozimbo Silveira; Saa, Antonio; Montes, José Maria Gascó; Caballero, Rafael; López, Francisca Guerrero (Pesquisa Agropecuaria Brasileira, 1999)
This study has been carried out at the Experimental Station "La Poveda" in Arganda del Rey (Madrid), with the following geographical coordinates: latitude 40º19' N; longitude 3º19' W Gr; and altitude 550 m. The main objective was to study the temporal variability of chemical properties in a soil with three cultivation systems. In order to study variation with time of chemical characteristics, samples were taken in February and September 1993 and February and September 1994. Organic matter content in the prairie/vetch-oat system had the smallest variation coefficient with respect to barley and vetch-oat/sunflower systems. Along with the time the barley/barley system presented a lower organic matter content. The crop systems pasture/vetch-oat and vetch-oat/sunflower presented an organic matter content 42.86 and 40.54% higher than that presented by barley/barley system, respectively.
Keywords: organic matter; humic acid; agricultural systems